Draft Genome Sequences of Lactococcus lactis Strains MS22314, MS22333, MS22336, and MS22337, Isolated from Fermented Camel Milk in Ethiopia - Bragason, Esben (Microbiol Resour Announc, 2020)
The genome sequences of four Lactococcus lactis strains isolated from fermented camel milk were sequenced using paired-end Illumina MiSeq reads. The genome size of each strain was about 2.6 Mb, and three of the strains were annotated with tet(S) coding for tetracycline resistance.